Green-light autofluorescence versus combined blue-light autofluorescence and near-infrared reflectance imaging in geographic atrophy secondary to age-related macular degeneration - Pfau, M; Goerdt, L; Schmitz-Valckenberg, S; Mauschitz, MM; Mishra, DK; Holz, FG; Lindner, M; Fleckenstein, M (Association for Research in Vision and Ophthalmology (ARVO), 2017)
Purpose: To compare the intermodality and interreader agreement for geographic atrophy (GA) lesion size quantification in green-light fundus autofluorescence (GAF; excitation = 518 nm) versus combined blue-light fundus autofluorescence (BAF; excitation = 488 nm) and near-infrared reflectance (NIR; 820 nm) –based grading.